Pelatihan Penyusunan Perangkat Pembelajaran Berbasis IT - Agung Pranoto; Rini Damayanti; Roely Ardiansyah; Kaswadi Kaswadi; Sueb Sueb (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
The Community Service Program (Penmas) aims to improve the ability of teachers in terms of learning tools, improve the ability of teachers to use IT, and improve teacher administration skills. The implementation of Penmas is preceded by providing information to the Chair of the Foundation about the training activities that will be carried out, giving invitations to teachers who will be training participants, carrying out training from January 19-20 2022, and making reports on the results of implementing activities. The materials presented during the training were: 1) Administrative urgency for educators, 2) IT-based learning tools. Participants also get guidance on writing learning tools in tutorial activities and practice writing learning tools. The training participants were 40 SMK and MA Tanada Foundation teachers.